Silk fibroin gel and preparation method thereof

By adding sodium hyaluronate and a cross-linking agent to the silk fibroin solution to prepare a gel and storing it in a sodium hyaluronate buffer solution, the problem of unstable mechanical properties of silk fibroin gel is solved, long-term stability and biocompatibility are achieved, and it is suitable for subcutaneous filling materials.

CN120617619AActive Publication Date: 2025-09-12BEIJING XINLIYAN BIOTECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202510854096.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-12
Estimated Expiration
2045-06-24

AI Technical Summary

Technical Problem

The existing chemically cross-linked silk fibroin gel has unstable mechanical properties during storage, easily becomes brittle, and cannot maintain the filling effect for a long time.

Method used

Sodium hyaluronate is added to the silk fibroin solution and incubated with cross-linking agents such as butanediol diglycidyl ether and divinyl sulfone to form a stable silk fibroin gel, which is then immersed in sodium hyaluronate injection buffer to maintain the hydration state and structural integrity of the gel.

Benefits of technology

The prepared silk fibroin gel maintains stable mechanical properties during long-term storage, is suitable as a tissue filling material, has excellent biocompatibility and collagen regeneration ability, and is suitable for subcutaneous injection filling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120617619A_ABST
    Figure CN120617619A_ABST
Patent Text Reader

Abstract

The invention provides silk fibroin gel and a preparation method thereof, and relates to the field of biological medicines.The preparation method comprises the steps that 1, degummed silk or regenerated silk fibroin is dissolved in a lithium bromide solution, and a silk fibroin solution is obtained; (2) adding a cross-linking agent and sodium hyaluronate into the silk fibroin solution, uniformly mixing, and incubating to obtain silk fibroin gel; wherein the use amount of the sodium hyaluronate is 2%-14% of that of the degummed silk or the regenerated silk fibroin. The silk fibroin gel prepared by the invention is stable in mechanical property, can be stably stored for a long time, and has excellent biocompatibility and filling property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedicine, and in particular to a silk fibroin gel and a preparation method thereof. Background Art

[0002] As we age, the elasticity and smoothness of the skin gradually decrease, leading to the formation of wrinkles and a gradual loss of surface radiance. To improve this situation, injectable fillers with minimal trauma, rapid recovery, and relatively simple operation are often used to increase soft tissue volume, eliminate, and improve wrinkles. Common injectable soft tissue fillers include collagen, sodium hyaluronate, polymethyl methacrylamide, calcium hydroxyapatite, and poly-L-lactic acid. Collagen and sodium hyaluronate, as bio-derived fillers, have good biocompatibility and few complications, but they are expensive, have high absorption rates, and have a short duration of effect. Synthetic fillers such as polymethyl methacrylamide, calcium hydroxyapatite, and poly-L-lactic acid have long-lasting effects, but due to poor biocompatibility, they may cause complications such as inflammation, infection, and foreign body granulomas.

[0003] Silk fibroin is derived from silkworm cocoons, a widely available and inexpensive raw material. Silk fibroin solutions can be converted into gels through existing chemical methods such as cross-linking, or physical methods such as ultrasound and shearing. Silk fibroin gels have excellent biocompatibility and can promote cell migration, collagen deposition, and angiogenesis, making them ideal for preparing injectable fillers. However, silk fibroin gels induced by physical methods have poor mechanical strength and poor filling effects after subcutaneous injection. Chemically cross-linked silk fibroin gels have excellent mechanical strength and, after being processed into gel particles, can achieve excellent filling effects through subcutaneous injection, showing great potential for application in the field of medical aesthetics. However, during storage, chemically cross-linked silk fibroin gels gradually become brittle and lose strength due to molecular conformational changes. This can cause the gel particles to rupture and lose their filling effect due to the inability to withstand the shear force of injection. Therefore, there is an urgent need to provide a silk fibroin gel with stable mechanical properties and a method for its preparation. Summary of the Invention

[0004] The embodiments of the present invention provide a silk fibroin gel and a preparation method thereof, which solve the problem that the current silk fibroin gel cannot maintain stable mechanical properties for a long time.

[0005] In a first aspect, the present invention provides a method for preparing a silk fibroin gel, the method comprising the following steps:

[0006] (1) dissolving degummed silk or regenerated silk fibroin in a lithium bromide solution to obtain a silk fibroin solution;

[0007] (2) adding a crosslinking agent and sodium hyaluronate to the silk fibroin solution, mixing and then incubating to obtain a silk fibroin gel; wherein the amount of sodium hyaluronate is 2% to 14% of the amount of degummed silk or regenerated silk fibroin.

[0008] Preferably, in step (1), the mass ratio of the degummed silk or regenerated silk fibroin to the lithium bromide solution is 1:(5-20).

[0009] Preferably, in step (1): the concentration of the lithium bromide solution is 6 to 13M.

[0010] More preferably, the concentration of the lithium bromide solution is 9-10M.

[0011] Preferably, in step (1), the molecular weight of the degummed silk or regenerated silk fibroin is 15 to 250 kDa.

[0012] Preferably, the molecular weight of the degummed silk or regenerated silk fibroin is 50-150 kDa.

[0013] Preferably, the amount of sodium hyaluronate used is 2% to 10% of the amount of degummed silk or regenerated silk fibroin used.

[0014] Preferably, in step (2): the cross-linking agent is butanediol diglycidyl ether and / or divinyl sulfone.

[0015] More preferably, the cross-linking agent is butanediol diglycidyl ether.

[0016] Preferably, in step (2): the molecular weight of the sodium hyaluronate is 200 to 3000 kDa.

[0017] More preferably, the molecular weight of the sodium hyaluronate is 1000-2000 kDa.

[0018] Preferably, in step (2), the amount of the cross-linking agent is 0.5% to 25% of the amount of the degummed silk or regenerated silk fibroin.

[0019] Preferably, in step (2): the incubation temperature is 55-65° C. and the incubation time is 2-4 h.

[0020] Preferably, after step (2), the method further includes:

[0021] The silk fibroin gel is soaked in a buffer solution, and then cut through a sieve to obtain gel particles, and the gel particles are dispersed in a sodium hyaluronate injection buffer solution, and sterilized to obtain a silk fibroin gel dispersion.

[0022] Preferably, the molecular weight of the sodium hyaluronate in the sodium hyaluronate injection buffer is 500 to 1500 kDa.

[0023] More preferably, the molecular weight of the sodium hyaluronate in the sodium hyaluronate injection buffer is 1000-1500 kDa.

[0024] Preferably, the buffer salts used in the buffer solution and the sodium hyaluronate injection buffer solution are at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and dipotassium hydrogen phosphate.

[0025] More preferably, the buffer salts used in the buffer solution and the sodium hyaluronate injection buffer solution are both disodium hydrogen phosphate and potassium dihydrogen phosphate.

[0026] More preferably, the pH of the buffer solution and the sodium hyaluronate injection buffer solution are both 6.0 to 7.5.

[0027] Preferably, the sodium hyaluronate injection buffer further includes an osmotic pressure regulator.

[0028] More preferably, the osmotic pressure regulator is at least one of sodium chloride and potassium chloride.

[0029] More preferably, the amount of the osmotic pressure regulator accounts for 0% to 0.9% of the mass of the sodium hyaluronate injection buffer.

[0030] Preferably, the mass ratio of the gel particles to the sodium hyaluronate injection buffer is (2-8):1.

[0031] More preferably, the mass ratio of the gel particles to the sodium hyaluronate injection buffer is (3-5):1.

[0032] In a second aspect, the present invention provides a silk fibroin gel prepared by any of the preparation methods described in the first aspect.

[0033] In a third aspect, the present invention provides an application of the silk fibroin gel according to the second aspect, wherein the silk fibroin gel is used as a tissue filling material.

[0034] Compared with the prior art, the present invention has at least the following beneficial effects:

[0035] The present invention introduces sodium hyaluronate into the silk fibroin solution. The high hydrophilicity of sodium hyaluronate prevents conformational changes in the silk fibroin molecules, allowing the silk fibroin gel particles to maintain stable mechanical properties over the long term. The silk fibroin gel product prepared using this method is highly stable and can be stored stably for at least three months, facilitating product storage and promising industrialization prospects. Furthermore, the silk fibroin gel exhibits excellent biocompatibility and can be used as an injectable tissue filler.

[0036] Figures in the specification

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0038] Figure 1 This is a flow chart of a method for preparing a silk fibroin gel provided by one embodiment of the present invention;

[0039] Figure 2 This is an immunohistochemical staining image of type I collagen in tissue sections of the injection site of the silk fibroin gel provided in the embodiment of the present invention, the control group, and the HA group one month after injection;

[0040] Figure 3 Immunohistochemical staining of type III collagen in tissue sections of the injection site of the silk fibroin gel provided in the embodiment of the present invention, the control group, and the HA group one month after injection;

[0041] Figure 4 α-SMA immunohistochemical staining of tissue sections at the injection site of the silk fibroin gel provided by the embodiment of the present invention, the control group, and the HA group one month after injection;

[0042] Figure 5 This is the CD90 immunohistochemical staining of the tissue sections at the injection site of the silk fibroin gel provided by the embodiment of the present invention, the control group, and the HA group one month after injection. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] The present invention provides a method for preparing silk fibroin gel, such as Figure 1 As shown, the preparation method comprises the following steps:

[0045] (1) dissolving degummed silk or regenerated silk fibroin in a lithium bromide solution to obtain a silk fibroin solution;

[0046] (2) adding a crosslinking agent and sodium hyaluronate to the silk fibroin solution, mixing and incubating to obtain a silk fibroin gel; wherein the amount of sodium hyaluronate is 2% to 14% (for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or 14%) of the amount of degummed silk or regenerated silk fibroin.

[0047] In an embodiment of the present invention, sodium hyaluronate is introduced into the silk fibroin solution, and the high hydrophilicity of sodium hyaluronate prevents the conformational transformation of the silk fibroin molecules, so that the silk fibroin gel particles can maintain stable mechanical properties for a long time. In this way, the silk fibroin gel product prepared based on this method has good stability, is conducive to the storage of the product, and has better industrial prospects. At the same time, the silk fibroin gel has excellent biocompatibility and can be used for injectable tissue filling materials.

[0048] According to some preferred embodiments, in step (1): the mass ratio of degummed silk or regenerated silk fibroin to lithium bromide solution is 1:(5-20) (for example, it can be 1:5, 1:5.5, 1:6, 1:8, 1:10, 1:12, 1:14, 1:15, 1:16, 1:18 or 1:20).

[0049] According to some preferred embodiments, in step (1): the concentration of the lithium bromide solution is 6 to 13 M (for example, it can be 6 M, 6.5 M, 7 M, 8 M, 9 M, 10 M, 11 M, 11.5 M, 12 M, 12.5 M or 13 M).

[0050] According to some more preferred embodiments, the concentration of the lithium bromide solution is 9-10 M (for example, 9 M, 9.2 M, 9.5 M, 9.6 M, 9.8 M or 10 M).

[0051] In the present invention, experiments have confirmed that if the amount of lithium bromide solution used is too much or the concentration is too high, too many lithium ions and bromide ions will remain, and the residual ions may react with the cross-linking agent, reducing the cross-linking efficiency, resulting in a loose gel network and decreased mechanical properties; however, if the amount of lithium bromide solution used is too little or the concentration is too low, some of the degummed silk or regenerated silk fibroin will not be completely dissolved, and the subsequent silk fibroin gel will be easily broken and fractured.

[0052] According to some preferred embodiments, in step (1): the molecular weight of the degummed silk or regenerated silk fibroin is 15 to 250 kDa (for example, it can be 15 kDa, 20 kDa, 30 kDa, 40 kDa, 50 kDa, 100 kDa, 120 kDa, 150 kDa, 160 kDa, 180 kDa, 200 kDa, 220 kDa or 250 kDa).

[0053] In the embodiment of the present invention, in order to ensure that the prepared silk fibroin gel has chains long enough to build a stable network and avoid aggregation caused by excessive length, the molecular weight of the degummed silk or regenerated silk fibroin is selected to be 15-250 kDa. In this way, it can avoid the occurrence of network defects, a significant decrease in mechanical strength, and excessive degradation rate of the silk fibroin gel caused by too low a molecular weight, and the high viscosity of the silk fibroin solution caused by too high a molecular weight, which makes it difficult to mix evenly with the crosslinker / sodium hyaluronate, and even produces a brittle gel.

[0054] According to some preferred embodiments, the molecular weight of the degummed silk or regenerated silk fibroin is 50-150 kDa (for example, 50 kDa, 60 kDa, 70 kDa, 80 kDa, 90 kDa, 100 kDa, 110 kDa, 120 kDa, 130 kDa, 140 kDa or 150 kDa).

[0055] According to some preferred embodiments, in step (2): the cross-linking agent is butanediol diglycidyl ether and / or divinyl sulfone.

[0056] According to some preferred embodiments, in step (2): the amount of the cross-linking agent is 0.5% to 25% (for example, it can be 0.5%, 1%, 1.5%, 3%, 5%, 10%, 15%, 20% or 25%) of the amount of degummed silk or regenerated silk fibroin.

[0057] According to some more preferred embodiments, in step (2), the ratio of the amount of degummed silk or regenerated silk fibroin to the amount of the cross-linking agent is 2 g:0.44 g.

[0058] According to some more preferred embodiments, the cross-linking agent is butanediol diglycidyl ether.

[0059] According to some more preferred embodiments, the amount of sodium hyaluronate is 2% to 10% of the amount of degummed silk or regenerated silk fibroin (for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%).

[0060] In the embodiments of the present invention, it has been experimentally confirmed that if the amount of sodium hyaluronate is less than 2%, it is difficult to form sufficient physical entanglement or chemical crosslinking sites with silk fibroin, and the self-assembly of silk fibroin is dominant, forming a brittle network dominated by β-folding, and too little sodium hyaluronate will cause the silk fibroin gel to absorb more water, resulting in a loose structure and easy collapse. Therefore, the prepared silk fibroin gel is easily degraded and cannot maintain long-term stability. If the amount of sodium hyaluronate is higher than 14%, the excess sodium hyaluronate will destroy the self-assembly of silk fibroin, reduce compatibility, and cause cracks in the gel; and the strong hydrophilicity and steric hindrance of sodium hyaluronate interfere with the arrangement of silk fibroin molecular chains, and the overly soft hyaluronic acid chain dominates the network, resulting in deterioration of its mechanical properties; in addition, the excess hyaluronic acid solution will consume the crosslinking agent, thereby reducing the degree of crosslinking, and high concentrations of hyaluronic acid will affect cell survival. Therefore, the present invention limits the amount of sodium hyaluronate to 2% to 14% of the amount of degummed silk or regenerated silk fibroin.

[0061] According to some preferred embodiments, in step (2): the molecular weight of sodium hyaluronate is 200-3000 kDa (for example, it can be 200 kDa, 300 kDa, 500 kDa, 600 kDa, 800 kDa, 1000 kDa, 1500 kDa, 2000 kDa, 2200 kDa, 2500 kDa, 2600 kDa, 2800 kDa or 3000 kDa).

[0062] According to some more preferred embodiments, the molecular weight of sodium hyaluronate is 1000-2000 kDa (for example, it can be 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa or 2000 kDa).

[0063] In an embodiment of the present invention, if the molecular weight of sodium hyaluronate is lower than 200kDa, the silk fibroin gel prepared will reduce the mechanical strength due to the sparse network, and its degradation is too fast, which will also reduce biological activity. If the molecular weight of sodium hyaluronate is higher than 3000kDa, the silk fibroin gel prepared will increase the viscosity of the solution and inhibit the assembly of silk fibroin, which will then cause the mechanical strength of the silk fibroin gel to be reduced and difficult to degrade, and will also hinder the transmission of nutrients. Therefore, the present invention has a molecular weight of sodium hyaluronate of 200 to 3000kDa, which can not only make the interpenetrating network of silk fibroin and sodium hyaluronate synergistically enhance mechanical properties, but also have the functions of anti-inflammatory, promoting cell proliferation and migration, and matching tissue regeneration cycle.

[0064] According to some preferred embodiments, in step (2): the incubation temperature is 55-65°C (for example, 55°C, 58°C, 60°C, 62°C or 65°C), and the incubation time is 2-4h (for example, 2h, 2.5h, 3h, 3.5h or 4h).

[0065] According to some preferred embodiments, after step (2), the method further comprises:

[0066] The silk fibroin gel is soaked in a buffer solution, and then cut through a sieve to obtain gel particles, and the gel particles are dispersed in a sodium hyaluronate injection buffer solution, and sterilized to obtain a silk fibroin gel dispersion.

[0067] According to some preferred embodiments, the molecular weight of sodium hyaluronate in the sodium hyaluronate injection buffer is 500-1500 kDa (for example, 500 kDa, 550 kDa, 600 kDa, 800 kDa, 900 kDa, 1000 kDa, 1200 kDa, 1300 kDa or 1500 kDa).

[0068] According to some more preferred embodiments, the molecular weight of sodium hyaluronate in the sodium hyaluronate injection buffer is 1000-1500 kDa (for example, it can be 1000 kDa, 1050 kDa, 1100 kDa, 1150 kDa, 1200 kDa, 1250 kDa, 1300 kDa, 1350 kDa, 1400 kDa, 1450 kDa or 1500 kDa).

[0069] According to some preferred embodiments, the buffer salts used in the buffer solution and the sodium hyaluronate injection buffer solution are at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and dipotassium hydrogen phosphate.

[0070] It should be noted that at least one is any one or a mixture of any several in any proportion.

[0071] According to some more preferred embodiments, the buffer salts used in the buffer solution and the sodium hyaluronate injection buffer solution are both disodium hydrogen phosphate and potassium dihydrogen phosphate.

[0072] According to some more preferred embodiments, the pH of the buffer solution and the sodium hyaluronate injection buffer solution are both 6.0 to 7.5 (for example, 6.0, 6.2, 6.5, 6.6, 6.8, 7.0, 7.2 or 7.5).

[0073] In the present invention, by storing the silk fibroin gel particles in sodium hyaluronate injection buffer, the hydration state and structural integrity of the gel can be further maintained, the gel can be prevented from cracking and deformation, and the embrittlement caused by secondary crystallization of silk fibroin in the air can be inhibited. At the same time, storage in sodium hyaluronate injection buffer can protect biological activity and reduce the risk of inflammation by simulating the physiological environment.

[0074] According to some preferred embodiments, the sodium hyaluronate injection buffer further includes an osmotic pressure regulator.

[0075] According to some more preferred embodiments, the osmotic pressure regulator is at least one of sodium chloride and potassium chloride.

[0076] According to some more preferred embodiments, the amount of the osmotic pressure regulator is 0% to 0.9% (for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%) of the mass of the sodium hyaluronate injection buffer.

[0077] According to some preferred embodiments, the mass ratio of gel particles to sodium hyaluronate injection buffer is (2-8):1 (for example, it can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1 or 8:1).

[0078] According to some more preferred embodiments, the mass ratio of the gel particles to the sodium hyaluronate injection buffer is (3-5):1 (for example, it can be 3:1, 3.5:1, 4:1, 4.5:1 or 5:1).

[0079] In an embodiment of the present invention, by limiting the mass ratio of gel particles to sodium hyaluronate injection buffer to (2-8):1, the sterilized silk fibroin gel dispersion can be directly used as an injection filling liquid, which can reduce the resistance of the gel passing through the needle and avoid blockage, while reducing the injection push force and preventing the gel structure from being damaged by mechanical shearing.

[0080] The present invention also provides a silk fibroin gel and adsorption resin microspheres prepared by the preparation method provided by the present invention.

[0081] The present invention also provides an application of the silk fibroin gel prepared by any of the above methods, wherein the silk fibroin gel is used as a tissue filling material.

[0082] According to some preferred embodiments, the silk fibroin gel dispersion is used as an injectable soft tissue filler.

[0083] In order to more clearly illustrate the technical solutions and advantages of the present invention, a silk fibroin gel and a preparation method thereof are described in detail below through several embodiments.

[0084] Example 1

[0085] 2 g of degummed silk or regenerated silk fibroin (molecular weight 75 kDa) was dissolved in 10 mL of LiBr solution (concentration 9.3 M) and incubated at 55-65° C. for 1-2 h. After the degummed silk or regenerated silk fibroin was completely dissolved, a silk fibroin solution was obtained. 0.44 g of butanediol diglycidyl ether (BDDE) and 0.04 g of sodium hyaluronate (HA) (molecular weight 1500 kDa) were then added and incubated at 55-65° C. for 2-4 h to obtain a silk fibroin gel (SF-HA (2%)). The gel was cut into small pieces, immersed in a buffer solution, dialyzed to remove residual reagents, and then cut through a sieve to obtain gel particles. Finally, the gel particles were dispersed in sodium hyaluronate injection buffer solution (pH 7.0, molecular weight of sodium hyaluronate 1000 kDa), sterilized at 121° C. for 15 min, and stored.

[0086] Example 2

[0087] Example 2 is basically the same as Example 1, except that the amount of sodium hyaluronate used is 0.1 g, and silk fibroin gel (SF-HA (5%)) is obtained.

[0088] Example 3

[0089] Example 3 is basically the same as Example 1, except that the amount of sodium hyaluronate used is 0.2 g, and silk fibroin gel (SF-HA (10%)) is obtained.

[0090] Example 4

[0091] Example 4 is basically the same as Example 3, except that the molecular weight of the sodium hyaluronate used for cross-linking is 200 kDa.

[0092] Example 5

[0093] Example 5 is basically the same as Example 3, except that the molecular weight of the sodium hyaluronate used for cross-linking is 1500 kDa.

[0094] Example 6

[0095] Example 6 is basically the same as Example 3, except that the molecular weight of the sodium hyaluronate used for cross-linking is 3000 kDa.

[0096] Example 7

[0097] Example 7 is basically the same as Example 3, except that the molecular weight of the sodium hyaluronate used for cross-linking is 200 kDa, and the cross-linking agent is divinyl sulfone (DVS).

[0098] Example 8

[0099] Example 8 is basically the same as Example 3, except that the molecular weight of the sodium hyaluronate used for cross-linking is 1500 kDa, and the cross-linking agent is divinyl sulfone (DVS).

[0100] Example 9

[0101] Example 9 is basically the same as Example 3, except that the molecular weight of the sodium hyaluronate used for cross-linking is 3000 kDa, and the cross-linking agent is divinyl sulfone (DVS).

[0102] Example 10

[0103] Example 10 is basically the same as Example 3, except that degummed silk or regenerated silk fibroin with a molecular weight of 15 kDa is used.

[0104] Example 11

[0105] Example 11 is basically the same as Example 3, except that degummed silk or regenerated silk fibroin with a molecular weight of 50 kDa is used.

[0106] Example 12

[0107] Example 12 is basically the same as Example 3, except that degummed silk or regenerated silk fibroin with a molecular weight of 150 kDa is used.

[0108] Example 13

[0109] Example 13 is basically the same as Example 3, except that degummed silk or regenerated silk fibroin with a molecular weight of 250 kDa is used.

[0110] Comparative Example 1

[0111] 2 g of degummed silk or regenerated silk fibroin (molecular weight 75 kDa) was dissolved in 10 mL of LiBr solution (concentration 9.3 M) and incubated at 55-65°C for 1-2 h. After the degummed silk or regenerated silk fibroin was completely dissolved, a silk fibroin solution was obtained. 0.44 g of butanediol diglycidyl ether (BDDE) was then added and incubated at 55-65°C for 2-4 h to obtain a silk fibroin gel (SF-HA (0%)). The gel was cut into small pieces, immersed in buffer, dialyzed to remove residual reagents, and finally immersed in sodium hyaluronate injection buffer (pH 7.0, molecular weight of sodium hyaluronate 1000 kDa), sterilized at 121°C for 15 min, and stored.

[0112] Comparative Example 2

[0113] Comparative Example 2 is basically the same as Example 1, except that the amount of sodium hyaluronate used is 0.3 g, and silk fibroin gel (SF-HA (15%)) is obtained.

[0114] Comparative Example 3

[0115] Comparative Example 3 is substantially the same as Example 1, except that the molecular weight of the degummed silk or regenerated silk fibroin is 10 kDa.

[0116] Comparative Example 4

[0117] Comparative Example 4 is substantially the same as Example 1, except that the molecular weight of sodium hyaluronate is 150 kDa.

[0118] The silk fibroin gel obtained in the above examples and comparative examples was cut with a sieve with an aperture of 150 microns to obtain silk fibroin gel particles, and then the gel particles were dispersed in sodium hyaluronate injection buffer. By detecting the hyaluronic acid content and properties in the silk fibroin gel particles, and the silk fibroin gel particles dispersed in the same concentration of sodium hyaluronate injection buffer were kept under different storage conditions and for different times, their long-term stability was evaluated. The results are shown in Table 1; Table 2 shows the effects of different molecular weights of sodium hyaluronate and different cross-linking agents on the physicochemical stability of the silk fibroin gel particles. After the silk fibroin gel particles prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were stored in the same concentration of sodium hyaluronate injection buffer for different times, the compressive stress-strain curve of the sample was measured at room temperature (25°C) using a universal testing machine (MTS-E44) (compression rate 5mm / min), and the Young's modulus was calculated based on the experimental results. The specific data are shown in Table 3. Wherein, the sodium hyaluronate content is the content of sodium hyaluronate in the silk fibroin gel particles.

[0119] Table 1

[0120]

[0121] Table 2

[0122]

[0123] Table 3

[0124]

[0125] As can be seen from Table 1, when the amount of sodium hyaluronate is 2% to 10% of the amount of degummed silk or regenerated silk fibroin, a cross-linked gel with stable physical and chemical properties can be prepared, which is convenient for the development and use of subsequent products. As can be seen from Comparative Example 2, when the amount of sodium hyaluronate is 15% of the amount of degummed silk or regenerated silk fibroin, the silk fibroin gel particles dispersed in the sodium hyaluronate injection buffer are placed at 30°C for 3 months. The properties of the gel change significantly, and there are very small white particles in the colloid. The possible reason is that the sodium hyaluronate concentration is too high, which affects the cross-linking stability of the silk fibroin, and the silk fibroin precipitates during the placement process, which is not conducive to the development of subsequent products. In Comparative Example 3, the degummed silk or regenerated silk fibroin with a molecular weight of 10kDa cannot form a gel; Comparative Example 4 forms a white gel, and after the white gel particles dispersed in the sodium hyaluronate injection buffer are placed at 30°C for 3 months, the elasticity of the gel particles is significantly reduced.

[0126] As shown in Table 2, when the sodium hyaluronate dosage is 10% of the degummed silk, both BDDE and DVS crosslinkers can produce crosslinked gels with stable physical and chemical properties when crosslinked with silk fibroin. The crosslinking ability is not affected by the molecular weight of the sodium hyaluronate. Similarly, the silk fibroin gels prepared in Examples 10 to 13 remained colorless and transparent after three months of storage at 30°C.

[0127] Young's modulus reflects the ability of a material to resist deformation under external forces. As shown in Table 3, the Young's modulus of silk fibroin gel SF-HA (0%) and silk fibroin gel SF-HA (2%) decreased significantly after one month of storage, and then remained stable. This proves that pure silk fibroin gel and silk fibroin gel with low sodium hyaluronate content have extremely poor mechanical stability after storage, are easily deformed under external forces, and cannot provide sufficient support after subcutaneous injection, resulting in poor product stability. After one month of storage, the Young's modulus of silk fibroin gel SF-HA (5%) decreased by about 30%, and after three months of storage, the Young's modulus decreased by about 50%. This trend shows that increasing the sodium hyaluronate content is conducive to maintaining the stability of the mechanical properties of silk fibroin hydrogel. After one month of storage, the Young's modulus of silk fibroin gel SF-HA (10%) increased significantly from 28.5kPa to 76.4kPa. This may be because the high sodium hyaluronate concentration in the freshly prepared silk fibroin gel SF-HA (10%) sample prevented its chains from fully stretching. After immersion, as the sample swelled, the sodium hyaluronate chains fully stretched, increasing the Young's modulus. Furthermore, after three months of storage, its Young's modulus remained around 70 kPa, showing no significant decrease. This demonstrates that the mechanical properties of the silk fibroin gel SF-HA (10%) remain stable even after prolonged storage, providing sufficient support after subcutaneous injection.

[0128] In addition, a silk fibroin gel SF-HA (10%) was prepared according to Examples 1 to 3. A dispersion of the silk fibroin gel SF-HA (10%) in sodium hyaluronate injection buffer (the mass ratio of gel particles to sodium hyaluronate injection buffer was 4:1) was injected subcutaneously into rats using a 26G needle. One month after the injection, the rats were sacrificed, and the tissues at the injection sites were collected, embedded, and sectioned for immunohistochemical staining. Figure 2 and Figure 3 The following are immunohistochemical staining of type I and type III collagen in tissue sections of the injection site 1 month after injection. Figure 2 and Figure 3 As can be seen, within the subcutaneous space at the injection site, a large amount of type I and type III collagen was produced between the microspheres in each silk fibroin gel group, demonstrating its excellent ability to induce collagen regeneration. In contrast, no type I and type III collagen was produced within the commercial sodium hyaluronate group (i.e., the HA group, which was injected with only sodium hyaluronate injection buffer). This suggests that silk fibroin gel has a better ability to induce collagen regeneration than sodium hyaluronate.

[0129] Figure 4 and Figure 5 The following are immunohistochemical staining of α-SMA and CD90 in tissue sections of the injection site 1 month after injection. α-SMA and CD90 are markers of fibroblasts. Figure 4 and Figure 5As can be seen, at the subcutaneous injection site, a large amount of α-SMA and CD90 were expressed between the microspheres of each silk fibroin gel group, proving that a large number of fibroblasts had migrated between the silk fibroin gel microspheres. In contrast, the commercial sodium hyaluronate group (i.e., the HA group, which only received sodium hyaluronate injection buffer) had almost no α-SMA and CD90 expression at the injection site. This shows that silk fibroin gel can induce fibroblasts to migrate to the injection area and induce them to produce type I and type III collagen, while commercial sodium hyaluronate injection fillers have difficulty inducing fibroblast migration to the injection area.

[0130] It should be noted that Figures 2 to 5 The control group is the control group, that is, rats that did not receive any treatment. The tissues at the injection site were embedded and sectioned and then immunohistochemically stained. Figures 2 to 5 The scale bars are all 200 μm.

[0131] Finally, it should be noted that the above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may be modified or some of the technical features thereof may be replaced with equivalents. Such modifications or replacements do not deviate from the essence of the corresponding technical solutions and the spirit and scope of the technical solutions of the various embodiments of the present invention. Any portions of the present invention not described in detail are well known to those skilled in the art.

Claims

1. A method for preparing a silk fibroin gel, characterized in that: include: (1) dissolving degummed silk or regenerated silk fibroin in a lithium bromide solution to obtain a silk fibroin solution; (2) adding a crosslinking agent and sodium hyaluronate to the silk fibroin solution, mixing and then incubating to obtain a silk fibroin gel; wherein the amount of sodium hyaluronate is 2% to 14% of the amount of degummed silk or regenerated silk fibroin.

2. The preparation method according to claim 1, characterized in that In step (1): The mass ratio of the degummed silk or regenerated silk fibroin to the lithium bromide solution is 1:(5-20); and / or, The concentration of the lithium bromide solution is 6 to 13M, preferably 9 to 10M.

3. The preparation method according to claim 1, characterized in that In step (1): The molecular weight of the degummed silk or regenerated silk fibroin is 15 to 250 kDa, preferably 50 to 150 kDa; and / or, The dosage of sodium hyaluronate is 2% to 10% of the dosage of degummed silk or regenerated silk fibroin.

4. The preparation method according to claim 1, characterized in that In step (2): The cross-linking agent is butanediol diglycidyl ether and / or divinyl sulfone, preferably butanediol diglycidyl ether; and / or, The molecular weight of the sodium hyaluronate is 200 to 3000 kDa, preferably 1000 to 2000 kDa.

5. The preparation method according to claim 1, characterized in that In step (2): The amount of the cross-linking agent is 0.5% to 25% of the amount of the degummed silk or regenerated silk fibroin; and / or, The incubation temperature is 55-65° C. and the incubation time is 2-4 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that Also includes: The silk fibroin gel is soaked in a buffer solution, and then cut through a sieve to obtain gel particles, and the gel particles are dispersed in a sodium hyaluronate injection buffer solution, and sterilized to obtain a silk fibroin gel dispersion.

7. The preparation method according to claim 6, characterized in that The molecular weight of the sodium hyaluronate in the sodium hyaluronate injection buffer is 500 to 1500 kDa, preferably 1000 to 1500 kDa; and / or, The buffer salts used in the buffer solution and the sodium hyaluronate injection buffer solution are at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and dipotassium hydrogen phosphate, preferably disodium hydrogen phosphate and potassium dihydrogen phosphate; more preferably, the pH of the buffer solution and the sodium hyaluronate injection buffer solution are both 6.0-7.

5.

8. The preparation method according to claim 6, characterized in that The sodium hyaluronate injection buffer further includes an osmotic pressure regulator; Preferably, the osmotic pressure regulator is at least one of sodium chloride and potassium chloride; More preferably, the amount of the osmotic pressure regulator accounts for 0% to 0.9% of the mass of the sodium hyaluronate injection buffer.

9. The preparation method according to claim 6, characterized in that The mass ratio of the gel particles to the sodium hyaluronate injection buffer is (2-8):1, preferably (3-5):

1.

10. A silk fibroin gel, characterized in that The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silk-fibroi and hyaluronic-acid (HA) composite gel for injection and preparation and application thereof

    CN102836465A

  • Fast preparation method of silk fibroin-hyaluronic acid complex gel

    CN106492279A

  • Silk fibroin composite gel for injection

    CN113877001A

  • Regenerated silk fibroin-sodium hyaluronate gel for injection and preparation method thereof

    CN117771436A

  • A preparation method of silk fibroin-hyaluronic acid filler for injection

    CN119770740A

Cited By

  • Stable silk fibroin liquid state condensation body and gel, and preparation method and application of stable silk fibroin liquid state condensation body and gel

    CN121135853A

  • A stable silk fibroin liquid condensate, gel, its preparation method and application

    CN121135853B